Anatomical Footprint of the Tibialis Anterior Tendon: Surgical Implications for Foot and Ankle Reconstructions. (4th June 2017) - Willegger, Madeleine; Seyidova, Nargiz; Schuh, Reinhard; Windhager, Reinhard; Hirtler, Lena
Abstract : This study aimed to analyze precisely the dimensions, shapes, and variations of the insertional footprints of the tibialis anterior tendon (TAT) at the medial cuneiform (MC) and first metatarsal (MT1) base. Forty-one formalin-fixed human cadaveric specimens were dissected. After preparation of the TAT footprint, standardized photographs were made and the following parameters were evaluated: the footprint length, width, area of insertion, dorsoplantar location, shape, and additional tendon slips. Twenty feet (48.8%) showed an equal insertion at the MC and MT1, another 20 feet (48.8%) had a wide insertion at the MC and a narrow insertion at the MT1, and 1 foot (2.4%) demonstrated a narrow insertion at the MC and a wide insertion at the MT1. Additional tendon slips inserting at the metatarsal shaft were found in two feet (4.8%). Regarding the dorsoplantar orientation, the footprints were located medial in 29 feet (70.7%) and medioplantar in 12 feet (29.3%). The most common shape at the MT1 base was the crescent type (75.6%) and the oval type at the MC (58.5%). The present study provided more detailed data on the dimensions and morphologic types of the tibialis anterior tendon footprint. The established anatomical data may allow for a safer surgical preparation and a more anatomical reconstruction.